Potential and Strategies for Developing Muslim-Friendly Tourism in West Java - Ode, Haruni; Fildansyah, Rully; Bunyamin, Ilham Akbar (Westscience Press, 2025)
This study examines the feasibility and method of developing Muslim-friendly tourism in West Java, Indonesia, a culturally rich region with natural landscapes and a majority Muslim population. A qualitative research method was employed whereby data were collected from government officials, tourism operators, and representatives of local communities using semi-structured interviews, participant observation, and document analysis. The findings of the research show that West Java's natural beauty, Islamic heritage sites, and halal food culture are firm foundations of Muslim-friendly tourism development. However, the research also reveals some primary challenges like fragmented application of policy, uneven levels of infrastructure quality, poor stakeholder coordination, and varying levels of awareness among small and medium enterprises regarding halal certification processes. The analysis further highlights the vital significance of socio-cultural harmonious matching and peoples' involvement, whereby local communities, particularly pesantren-based networks, are directly involved in promoting ethical and value-based tourism culture. To fill in the gaps identified, the study recommends five strategic directions: (1) improving branding and marketing communication to market West Java as a Muslim-friendly inclusive destination, (2) increasing capacity-building programs for tourism stakeholders, (3) improving infrastructure and preparedness of services, (4) building multi-stakeholder partnerships, and (5) establishing a provincial halal tourism task force to enable coordinated implementation. The study determines that comprehensive and inclusive Muslim-friendly tourism development in West Java requires a strategy that reconciles regional religious values with global tourism norms. Through doing this, the province will be able to enhance its competitiveness in the global halal tourism market while nurturing social harmony, cultural authenticity, and economic empowerment.